Biological Characterization of Hepatitis B virus Genotypes: Their Role in Viral Replication and Antigen Expression - Elizalde, María Mercedes; Tadey, Luciana; Mammana, Lilia; Quarleri, Jorge Fabián; Campos, Rodolfo Héctor; Flichman, Diego Martín (Frontiers in Microbiology, 2021)
Hepatitis B virus (HBV) inter-host evolution has resulted in genomic diversification reflected in the existence of nine genotypes (A-I) and numerous subgenotypes. There is growing evidence that genotypes influence HBV natural history, clinical outcomes, and treatment response. However, the biological characteristics underlying these differences have not yet been established. By transfecting HuH-7 cells with unit-length constructs of genotypes A2, B2, C1, D1, and F1b, we identified major differences in HBV replicative capacity and antigen expression across genotypes. Genotypes B2 and F1b showed a 2-fold increase in cccDNA levels compared to the other genotypes (p<0.005). Genotype A2 expressed the lowest pgRNA levels, with a 70-fold decrease in relation to the other genotypes (p<0.0001), while genotype B2 showed the lowest Precore RNA levels, with a 100-fold reduction compared to genotype A2 (p<0.0001). The highest intracellular HBV DNA levels were observed for genotype B2 and the lowest for genotypes A2 and C1 (p<0.0001). Regarding antigen expression, genotype F1b secreted the highest HBsAg levels and genotype D1 the lowest (p<0.0001), while genotypes A2 and B2 showed the highest intracellular HBsAg levels (p<0.0001). Interestingly, genotype C1 secreted the highest HBeAg levels, while genotype A2 showed the highest intracellular levels (p<0.0001). Finally, the analysis of the intra/extracellular antigen ratios revealed that most genotypes retained intracellularly 5–20% of the antigens, except the genotype A2 that retained 50% of the total expressed antigens. In conclusion, this study provides new insights into the biological characteristics of HBV genotypes, being the first study to comparatively analyze European (A and D) and Asian (B and C) genotypes with the Latin American (F) genotype. The differences in HBV replication and antigen expression might contribute to understand the differential role of genotypes in pathogenesis.